Superb Microvascular Imaging: Added Value and Novel Applications - Artul,Suheil; Nseir,William; Armaly,Zaher; Soudack,Michalle
Determining the presence and characteristics of vascular flow is an essential part of sonography interrogation. However, small vessels and low velocities are not always possible to depict with conventional color and power Doppler ultrasound. This can be frustrating, especially when the diagnosis depends mainly on the existence of vascular flow, the sonographic examination will be inconclusive, further imaging examinations will be required and diagnosis delayed. Superb microvascular imaging (SMI) is a novel vascular imaging mode, which provides visualization of low velocity and microvascular flow. SMI uses a clutter suppression algorithm to extract flow signals and depicts this information as a color overlay image or as a monochrome or color map of flow. By using SMI, high frame rates and high-resolution images remain maintained. With SMI, it is possible to visualize small vessels including their branches that, until now, it is possible to demonstrate only using contrast-enhanced ultrasound. Availability of this additional technology on all ultrasound machines may make some of the computed tomography scans unnecessary. In our paper, we describe six patients, aged 16–73 years, in which final diagnosis was achieved only with SMI and where conventional color and power Doppler failed. All these examinations were performed using Aplio 500 Platinum ultrasound unit (Toshiba Medical Systems, Tokyo, Japan).